Określanie kosztu kapitału własnego za pomocą arbitrażowego modelu wyceny (arbitrage pricing model - APM) - Byrka-Kita, Katarzyna (Arbitrage Pricing Model as a Tool in the Process of Cost of Equity Estimation, 2005)
The article presents the logic and assumptions of the arbitrage pricing model (АРМ). Furthermore the estimation techniques which are used with reference to АРМ were presented. Because in the case of АРМ the model and estimation methodology ате tested simultaneously, the results of the APT tests were described. In the final part of the paper the two competing methodologies, АРМ and CAPM, were compared.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 30-47